The kanban playbook : a step-by-step guideline for the lean practitioner - Ortiz, Chris A. (Lean playbook series., 2016)
Ideal for Lean practitioners and facilitators looking for a training tool and guideline that can be used in the work area while improvements are being made, this book includes color images and a combination of short paragraphs and bulleted points to walk you step-by-step through the process of implementing Kanban to reduce waste and bring about remarkable changes in your organization. --